Mechanical Properties of Plastic Sand Brick Containing Plastic Waste - Kameshwar Sahani; Bhesh Raj Joshi; Kabiraj Khatri; Abiraj Thapa Magar; Sabin Chapagain; Nabanita Karmacharya (Advances in Civil Engineering)
The use of plastic has grown extensively in recent years all over the world. It is inexpensive and easily available and can be moulded into any shape. However, plastic is nonbiodegradable; it causes pollution and create difficulties in managing even for a wealthy nation. The purpose of this study was to investigate the environment-friendly potential use of plastic and demonstrate usefulness of plastic sand bricks as alternative structural elements, replacing standard clay brick. The physical and mechanical properties of plastic sand bricks were studied in different plastic sand ratios of 1 : 3, 1 : 4, and 1 : 5 by their weight, using plastic as a binder. Moreover, the thermal resistance test, split tensile strength test, penetration test, and Fourier transform infrared spectroscopy were performed. The study concluded that the strength of plastic sand brick depends upon the uniformity of the mixture and increases when the ratio of sand and plastic in the mixture is increased to 1 : 4 from 1 : 3. Any increase or decrease in the ratio 1 : 4 is found to reduce the strength. All the bricks in any of the ratios showed zero water absorption and nil efflorescence.